De la mise au silence à la prise de parole : la voix féminine de Martin Crimp à Sarah Kane - Solange Ayache (Sillages Critiques)
Dramatic experiments with the voice in the theatres of Martin Crimp (Attempts on Her Life, 1997; Fewer Emergencies, 2005) and Sarah Kane (Crave, 1998; 4.48 Psychosis, 2000) fall within the scope of a post-Beckettian quest for new formal constraints for the text and the stage. While the dramatic space, for both Crimp and Kane, is no longer a physical space but has become, to use Crimp’s words, “a mental space”, it appears that the scenic space has transformed into a sheer vocal space. This article looks at the importance of the voice in Crimp’s and Kane’s texts, focusing on the intervocal and transdramatic space created between their plays around the voice of a woman both central and spectral. No longer a conventional character, the female subject, whose voice is either heard as a broken embodied token of a disturbed mind, or is silenced and replaced by the alienating narratives of others, is but a mere shadow, vestige or vocal image of herself. Polyonymous in Attempts on Her Life, anonymous in 4.48 Psychosis, “Anne”, as I will argue, is eclipsed in a post-traumatic silence in Crimp’s play, then restored on the front of a sacrificial stage in Kane’s, regaining her own power of speech in a poetic language made of echoes. Her voice, fully expanding in the space although pierced with blanks and holes, is the ultimate dramatic event. In these two plays as well as in Kane’s Crave and Crimp’s Fewer Emergencies, the voice thus appears at the core of what could be called a “psychopoetics” of the stage.